Relationship between Vitamin B6 Intake and LDL Levels of CHD - Wira Maria Ginting; Ika Juita Sembiring (JURNAL KESMAS DAN GIZI (JKG), 2019)
Heart disease results from a continuous process, the heart gradually loses its ability to function normally. Early in the heart disease compensates for its inability to function and maintains normal blood circulation through an enlarged and increased pulse (compensated heart disease) (Inayati, 2014). The aim of the study was to determine the relationship between vitamin B6 intake and LDL levels in patients with coronary heart disease. This study was observational with a cross sectional design. Data on vitamin B6 intake obtained by the food recall method for 3 days. Data processing is done by person correlation test. The results showed that vitamin B6 intake of coronary heart disease (CHD) patients in hospitals. Dr. Pringadi Medan is 60% good and 35% is not good. Chronic LDL levels vary, 10% are normal, 65% are mid and 25% are high. The results of statistical tests showed that there was no relationship between vitamin B6 intake and LDL levels.